PENGARUH KOMITMEN ORGANISASI, SISTEM ADMINISTRASI, SUMBERDAYA, PENGHARGAAN, SANKSI, DAN MOTIVASI TERHADAP PENYUSUNAN APBD BERBASIS KINERJA DI KABUPATEN BATANGHARI - . Muryati (Jurnal Akuntansi & Keuangan Unja, 2015)
This research intent to know and analyse the factor that influence of Budgeting of Regional Revenue Expenditure (APBD) process based on erformance at Batanghari Regency Government. With analyse that is done, therefore will get to know commitment of organization influence, administrasion system, human resources, reward, punishment, and motivation of Budgeting of Regional Revenue Expenditure (APBD)process based on performance at Batanghari Regency. This research is executed at Batanghari Regency Government by distributing questionnaires in each The Managerial Performance of the Work Unit (SKPD) to be filled by chief of The Managerial Performance of the Work Unit (SKPD) and planning division as respondents. Number of respondents is 104 of 52 The Managerial Performance of the Work Unit (SKPD) at Batanghari Regency. The result of this research proves that commitment of organization influence, administrasion system, human resources, reward, punishment, and motivation have an effect on significant  Budgeting of Regional Revenue Expenditure (APBD)process based on performance simultaneously. Partially, commitment of organization influence, administrasion system, human resources, reward, punishment, and motivation have an effect on significant  Budgeting of Regional Revenue Expenditure (APBD)process based on performance, but the one has the biggest influence to Budgeting of Regional Revenue Expenditure (APBD)process based on performance is punishment. The result of this research also proves that adjust R2 is 0,47, that is show that 47,4% of variety Budgeting of Regional Revenue Expenditure (APBD) process based on performance shown by variety of the six independent variable, commitment of organization influence, administrasion system, human resources, reward, punishment, and motivation, and the rest that 52,6% shown by other variable exclusive of the variable used. Keywords: Commitment of Organization, Administrasion System, Human Resources, Reward, Punishment, Motivation, Budgeting of Regional Revenue Expenditure (APBD) based on performance